Melting of Nanoprticle-Enhanced Phase Change Material inside Shell and Tube Heat Exchanger - Seiyed Mohammad Javad Hosseini; Ali Akbar Ranjbar; Kourosh Sedighi; Masoumeh Rahimi (Journal of Engineering)
This paper presents a numerical study of melting of Nanoprticle-Enhanced phase change material (NEPCM) inside a shell and tube heat exchanger using RT50 and copper particles as base material and nanoparticle, respectively. In this study, the effects of nanoparticles dispersion (, 0.03, and 0.05) on melting time, liquid fraction, and penetration length are investigated. The results show that the melting time decreases to 14.6% and the penetration length increases to 146% with increasing volume fraction of nanoparticle up to .